2013
DOI: 10.1039/c3ta11390f
|View full text |Cite
|
Sign up to set email alerts
|

High {001} facets dominated BiOBr lamellas: facile hydrolysis preparation and selective visible-light photocatalytic activity

Abstract: Efficient photocatalytic nanocrystals with high-ratio exposure of active facets have aroused a great number of research interests in recent years. However, most preparations of such materials need the addition of special capping agents (like surfactants) or harsh reaction conditions (such as hydrothermal reactions). In this work, a controllable synthesis of BiOBr nanosheets with a thickness from 9 nm to 32 nm was easily achieved in a hydrolysis system through adjusting temperature and solvent, without adding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
136
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(153 citation statements)
references
References 52 publications
14
136
0
3
Order By: Relevance
“…6b) also analyzedthe photocatalytic data of BiOBr, [7,20] BiOCl, [17] and Bi 3 O 4 Cl [13] nanosheetsin the literature, and a similar linear relationship was obtained for these literature samples (Fig. S13, Supporting information), although the literature authors ascribed their photoactivity enhancement to either the increasing exposure percentages of photoactive facets or the intensifying IEF.In association with our previous results about the linear dependence of the k on the nanosheet thickness for the BiOBr lamellas with highly exposed (001) facets [20], we can conclude that this inversely linear dependence of the k on the nanosheet thickness is irrelevant to the exposed facets of the nanosheets.Thus, the nanosheet thickness is a crucial factor influencing the photoactivity of 2Dsemiconductor photocatalysts.…”
Section: Thickness-dependence Of Photoactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…6b) also analyzedthe photocatalytic data of BiOBr, [7,20] BiOCl, [17] and Bi 3 O 4 Cl [13] nanosheetsin the literature, and a similar linear relationship was obtained for these literature samples (Fig. S13, Supporting information), although the literature authors ascribed their photoactivity enhancement to either the increasing exposure percentages of photoactive facets or the intensifying IEF.In association with our previous results about the linear dependence of the k on the nanosheet thickness for the BiOBr lamellas with highly exposed (001) facets [20], we can conclude that this inversely linear dependence of the k on the nanosheet thickness is irrelevant to the exposed facets of the nanosheets.Thus, the nanosheet thickness is a crucial factor influencing the photoactivity of 2Dsemiconductor photocatalysts.…”
Section: Thickness-dependence Of Photoactivitymentioning
confidence: 99%
“…[14][15][16]The controversy of photocatalytic mechanisminstudy of crystal facet engineering of semiconductors prominently resides in bismuth-based photocatalysts, especially bismuth oxyhalide (BiOX, X=Cl, Br or I) with highly exposed (001) facet.For instance, most researchers attributed the photoactivity enhancement of BiOX nanosheets to increasing exposure percentages of photoactive (001) facets; [7,9,17,18]Zhang et al thought the photoactivity of Bi 3 O 4 Cl nanosheets with highly exposed (001) facets and similar structure as BiOX nanosheets relied on themagnitude of internal electric field(IEF); [13]Xie et al ascribed the higher photoactivity of BiOCl nanosheets to the more vacancy associates on the surface of (001) facets. [19]Actually, for these sheet-like photocatalysts with highly exposed (001) facets, a prominent reduction of nanosheet thickness was observed along with the increase of the (001) facet exposure percentage, [7,9,17,18]the IEF magnitude [13]or the vacancy associate amount. [19]Recently, we investigatedthe relationship between the photoactivity of BiOBr lamellasandthe lamella thicknessand found that the photoactivity of the samples depended inversely proportionallyonthe lamella thickness.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,6 BiOCl has a tetragonal structure with lattice constants of a = b = 0.389 and c = 0.789 nm. In its crystal structure, a layer structure (parallel to {001} facets) characterized by [Bi 2 O 2 ] slabs is interleaved by double slabs of Cl atoms. 7 In general, different crystal facets with different electronic structures and geometric shape exhibit different intrinsic reactivities and surface physical and chemical properties related with the crystallographic orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al 19 selectively synthesized BiOCl single-crystalline nanosheets with exposed {001} and {010} facets via a facile hydrothermal route. Zhang et al 20 synthesized BiOBr nanosheets with thicknesses ranging from 9 to 32 nm by a facile and surfactant-free method, which shown higher photocatalytic activity to RhB under visible-light irradiation. Bi 2 O 2 CO 3 is a typical "SillĂ©n" phase, in which Bi-O layers and (CO 3 ) layers are inter-grown with the plane of the (CO 3 ) group orthogonal to the plane of the Bi-O layer.…”
Section: -17mentioning
confidence: 99%